PATRONASE DAN KLIENTELISME DALAM DUKUNGAN POLITIK TUANKU TAREKAT SYATHARIYAH PADA PILKADA DI SUMATERA BARAT - Rizki Herdi Kurniawan (Ensiklopedia Education Review, 2023)
This paper examines the political support given by Tuanku Tarekat Syathariyah in Padang Pariaman to candidate pairs in the Pilkada of West Sumatra. The support given by Tuanku Tarekat Syathariyah to Pilkada candidates is in the form of a pattern of patronage relations which is closely related to the practice of money politics. The support provided is also clientelistic in nature because Tuanku Tarekat Syathariyah also acts as a broker who collects support from students, congregations and other Tuanku- Tuanku for one of the Pilkada candidates. Using a qualitative approach through literature studies, this paper discusses political support with patterns of patronage and clientelism that cause the practice of money politics due to the two-way relationship built by providing mutual assistance. Candidates provide assistance in the form of coaching, protection of the Syathariyah congregation, assistance for the needs of traditional Syathariyah surau and Islamic boarding schools, which are then reciprocated by gathering and providing political support to candidates to win the Pilkada.Keywords: Tuanku Syathariyah Congregation, Pilkada, Patronage and Clientelism.